Manajemen Kelas Pembelajaran Seni Musik Barang Bekas Berbasis PjBL dengan Pendekatan Steam untuk Meningkatkan Kreativitas Siswa di Kelas IV SD Inpres 1 Tatura - ni luh dewi puspita; Kadek Hariana; Rizal; Surahman (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2023)
This study aims to improve student creativity in classroom management of PjBL-based music art learning with the STEAM approach. This type of research is Classroom Action Research (PTK) using the Kemmis and Mc. Tanggart research design. The subjects in this study were fourth grade students of SD Inpres 1 Tatura, totaling 23 students consisting of 12 male students and 11 female students. Data collection techniques used in this study were observation, interview, and documentation. Data analysis used student activity observation sheets, teacher activity observation sheets and student creativity observation sheets. The results of research on student creativity in cycle I obtained a classical completeness of student creativity of 65.21% and in cycle II increased with the acquisition of a classical completeness of student creativity of 78.26%. The results of teacher activity research in cycle I obtained 85.52% and in cycle II increased to 97.36%. The results of student activity research in cycle I were obtained at 69.56% and in cycle II increased to 78.26%. The resulting project is a used glass bottle musical instrument made in collaboration with PjBL-based students with a STEAM approach Based on these results it can be concluded that classroom management of PjBL-based second-hand musical art learning with a STEAM approach can increase student creativity in class IV SD Inpres 1 Tatura.